3D Flexible Frequency Selective Surface with Stable Electromagnetic Transmission Properties (Adv. Mater. Technol. 7/2022). Issue 7 (12th July 2022) - Fan, Xuanqing; Pan, Zijian; Chen, Sihong; Li, Yuhang; Zhao, Zhao; Pan, Taisong
Abstract : 3D Frequency Selective Surfaces In article number 2101316, Yuhang Li, Taisong Pan, and co‐workers present a 3D flexible frequency selective surface fabricated by releasing pre‐strains in the flexible substrate and thus buckling the 2D Jerusalem metal precursors locally bonded on it, capable of being conformally adhered to complex surfaces, which can maintain stable frequency‐selective properties as well as transmission performance when subjected to biaxial stretching strains.